PERLINDUNGAN HUKUM NASABAH DALAM PINJAM MEMIMJAM UANG SECARA ONLINE PADA APLIKASI KREDIT PINTAR PADA MASYARAKAT DI KOTA SEMARANG - Aditya Rifaldi; Adi Suliantoro (Jurnal Ilmiah Dinamika Hukum, 2023)
The background of this thesis is that it starts from the rapid growth of information technology-based lending service providers, apparently not balanced with adequate education to the public, causing various effects / risks that arise from the many kinds of online loans and there are still many unregistered or illegal organizing companies found as well as the potential for leaking user personal data that can be misused by the organizing company or another party One of the platforms is the Smart Credit App. The problems that the author raises in this study are How to Arrange Online Loans on the Smart Credit Application, How are the Losses arising from online borrowing of the Smart Credit Application and How is the Responsibility of the Smart Credit Application for Losses from Customers. The research method used by the author in answering problems is Normative Juridical Research where the author tries to examine problems with existing legal rules and uses the literature study method in collecting existing legal materials. The conclusion of this thesis research is that Online Loans through the Smart “Credit Application in the people of Semarang City are regulated in Article 1320 of the Civil Code which in essence stipulates thatagreements made online must still meet the legal requirements of an agreement. The implementation is regulated in POJK regulation 77/2016 concerning Technology-based Loan Services. Customer protection in online loan agreements can be found in the Consumer Protection Law in article 7 which regulates the Obligations of Business Actors, then Article 8 which regulates things that are prohibited from being done by Business Actors, and Article 18 which regulates the provisions of matters related to the Standard Clause. ITE Law, where in Article 11 and Article 17 of the ITE Law regulates matters related to the validity of electronic agreements, OJK Regulation Number 77 / POJK / 2016 concerning Services of a Loan in the form of Money Based on Information Technology which is regulated through article 18 concerning the Form and Structure of online loan agreements. The disadvantage that often arises from the Smart Credit Application is the dissemination of personal data carried out by the Smart Credit Application because the Debtor does not make payments on time, so the debt Collector uses techniques to use the dissemination of personal data to pressure the Debtor to immediately make payments, Juridical Responsibility The Kredit Pintar application for actions committed for defamation can be held civil liability through a Tort Lawsuit as stipulated in article” 1365 of the Civil Code filed by Customers who feel aggrieved because their identity is used in the misuse of personal data. Keywords : Online Loans, Smart Credit Applications.